Insect frass fertilizer upregulates maize defence genes and resistance against an invasive herbivore pest - Daniel Munyao Mutyambai; Johnstone Mutiso Mutua; Abdul A. Jalloh; Dennis Beesigamukama; Andre Kessler; Sevgan Subramanian; Thomas Dubois; Sunday Ekesi; Chrysantus M. Tanga (Scientific Reports)
Abstract The black soldier fly frass fertilizer (BSFFF) has gained global attention as a multipurpose input for soil fertilization and pest and disease management. However, there are limited studies that have examined its effects on insect pest resistance and the underlying mechanisms. We investigated the impact of amending soil with BSFFF on maize growth, defense gene expression and resistance to a polyphagous insect herbivore, Spodoptera frugiperda (Lepidoptera: Noctuidae) through larval feeding assay. Maize growth was evaluated by measuring plant height, chlorophyll concentration, and biomass accumulation in soils amended with BSFFF, synthetic fertilizers (Di-ammonium phosphate and Calcium ammonium nitrate) and unfertilized soils at various growth stages. Larval feeding assays were conducted using leaf discs from maize plants grown in different amended soils. The expression level of three maize defense genes: pathogenesis related protein 5 (pr-5), maize proteinase inhibitors (mpi), and lipoxygenase 3 (lox-3) were analyzed using quantitative polymerase chain reaction (qPCR) while yield was assessed through a field trial over two cropping seasons. Maize plants grown in BSFFF amended soils showed 30% more growth, higher chlorophyll, 0.93–2.86 t ha− 1 higher yield, and 48% better nitrogen use efficiency than from those in synthetic or unfertilized soils. Moreover, S. frugiperda larvae consumed significantly less leaf tissue from maize plants grown in BSFFF amended soils than synthetically fertilized and non-fertilized soils. Maize defense genes pr-5, mpi, and lox-3 were highly expressed both constitutively and inductively in maize planted in BSFFF amended soils compared to those grown in synthetically fertilized and non-fertilized soils. We observed a significant negative correlation between mpi gene expression and larval feeding, suggesting its role in maize resistance. Our results show that soil amendment with BSFFF strengthens plant defense systems and positively impacts plant growth and yield, contributing to increased agricultural productivity and sustainability.